Retinitis Pigmentosa: A Case Series - Shah, Jayashree S; RK, Niveditha; Sehgal, Shubham; HM, Lokesha (Journal of Contemporary Medical Practice, 2024)
Background: Retinitis Pigmentosa (RP) is a group of inherited retinal dystrophies (IRDs) characterized by progressive vision loss. Worsening symptoms are associated with increased difficulty in performing daily activities and reduced autonomy. This results in difficulties staying in work, higher levels of anxiety and depression, social isolation, and an overall reduced quality of life. Bardet Biedl syndrome and Usher syndrome are ciliopathies that can manifest with retinal degeneration. Case Presentation: Here, we report four patients who presented with a variety of clinical manifestations of retinitis pigmentosa. The first two patients presented with features of Bardet - Biedl syndrome, third patient presented with features of typical retinitis pigmentosa and fourth patient presented with features of Usher syndrome. Case 1: A case of 16yr old male patient admitted in medicine ward with microcytic hypochromic anaemia, referred to department of ophthalmology for diminution of vision in both the eye more during night time diagnosed as Bardet Biedl syndrome as he fulfilled five criteria of primary features (retinitis pigmentosa, obesity, mental retardation, polydactyly and features of hypogonadism) and one secondary feature (delayed developmental milestones). Case 2: A case of 9 year old male patient presented to ophthalmology OPD with diminution of vision in both eyes, more during night time, diagnosed as Bardet Biedl syndrome as he fulfilled four criteria of primary features (retinitis pigmentosa, central obesity, mental retardation and post axial polydactyly). CASE 3: A case of 57 year old male patient presented to ophthalmology OPD with loss of vision in left eye and diminution of vision in right eyes since 1 year diagnosed as typical Retinitis pigmentosa (RP). Case 4: A 21 year old male patient presented to Ophthalmology outpatient department with complaints of diminished vision in both eyes more at night since 5 years. He also had history of difficulty in hearing for last 3 years, diagnosed as Type II usher syndrome. Conclusion: The management of patients with RP is multidisciplinary and requires a focused and structured system where all healthcare providers involved in the care of patients closely collaborate. Disease monitoring, visual prognosis and enrollment of patients in upcoming and ongoing clinical trials are all steps that can be taken to aid the patient.